2022
DOI: 10.3390/pharmaceutics14081593
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Study of Solid Lipid Nanoparticles Based on Curcumin, Resveratrol and Capsaicin Containing Linolenic Acid

Abstract: Linolenic acid (LNA) is the most highly consumed polyunsaturated fatty acid found in the human diet. It possesses anti-inflammatory effects and the ability to reverse skin-related disorders related to its deficiency. The purpose of this work was to encapsulate LNA in solid lipid nanoparticles (SLNs) based on curcumin, resveratrol and capsaicin for the treatment of atopic dermatitis. These compounds were first esterified with oleic acid to obtain two moonoleate and one oleate ester, then they were used for SLN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Surfactants such as sodium lauryl sulfate (SLS), cetyltrimethylammonium bromide (CTAB), or polysorbate 80 and organic solvents such as ethanol, isopropyl alcohol, or acetone) are typically added to release media to enhance the drug solubility of the sink condition in in vitro drug release tests [ 61 ]. Several recent studies have reported the use of different release media containing ethanol up to 50% ( v / v ) to investigate the release profile of hydrophobic drugs [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Nasra et al [ 64 ] reported that the release medium containing 50% ( v / v ) ethanol is the most suitable for curcumin release (100% release) compared to the other release media containing various types of surfactants such as 0.5–1% w / v SLS or 30% w / v polyethylene glycol 400 (PEG 400).…”
Section: Resultsmentioning
confidence: 99%
“…Surfactants such as sodium lauryl sulfate (SLS), cetyltrimethylammonium bromide (CTAB), or polysorbate 80 and organic solvents such as ethanol, isopropyl alcohol, or acetone) are typically added to release media to enhance the drug solubility of the sink condition in in vitro drug release tests [ 61 ]. Several recent studies have reported the use of different release media containing ethanol up to 50% ( v / v ) to investigate the release profile of hydrophobic drugs [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Nasra et al [ 64 ] reported that the release medium containing 50% ( v / v ) ethanol is the most suitable for curcumin release (100% release) compared to the other release media containing various types of surfactants such as 0.5–1% w / v SLS or 30% w / v polyethylene glycol 400 (PEG 400).…”
Section: Resultsmentioning
confidence: 99%
“…The fabrication of solid lipid nanoparticles can be carried out by microemulsification, which consists of the initial mixing of the hot ester with the surfactants (Tween 20, butanol and sodium taurocholate) at 70 °C. The nanoparticles are formed by dispersing the resulting mixture in cold water under mechanical agitation at high speed [ 24 ]. The substances used are reported in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The results of these studies showed a reduction in AD symptoms, inflammation, oxidative damage, and inflammatory cytokines in the in vivo AD model [ 93 ]. Recently, nanoparticles combined with resveratrol, containing linolenic acid or hyaluronic acid hydrogel, have been designed as new tools for AD treatment [ 94 , 95 ].…”
Section: Nutraceuticals and Atopic Dermatitis (Ad)mentioning
confidence: 99%